The Impact of COVID-19 Third Dose Vaccination on the Magnitude of Antigen Specific T Cells in Kidney Transplant Patients - Girmanova, E; Duskova, J; Mrazova, P; Fialova, M; Viklicky, O; Hruba, P (Physiological research, 2024)
Measuring T cell response can add information about antivirus immunity provided by antibody test results. The study evaluates the impact of a third mRNA COVID-19 vaccine dose on T cell response and antibody production in kidney transplant recipients (25 KTRs) versus healthy controls (26 Hc). Results show a significant rise in S-activated CD4+CD154+IFN?+TNF?+ double producer cells in both KTRs (p=0.025) and Hc (p=0.009) as well as increased spike antibody response in KTRs (p=0.00019) and Hc (p=3.10-8) third-month post-third dose. Moreover, the study revealed a drop in seronegative KTRs (non-responders) from 9/25 (36%) pre-third dose to 2/25 (7%) at 3 months post-third dose while 5/9 (56%) of non-responders post-second dose showed specific T cell responses. Notably, the third dose significantly improved seroconversion rates in both KTRs and Hc, although Hc individuals exhibited higher antibody levels. Key words: mRNA COVID-19 vaccine, T cells, SARS-CoV-2 antibodies, Kidney transplantation, mRNA vaccination.
Keywords: vakcinace; Humans; lidé středního věku; T-Lymphocytes; Vaccination; Female; Aged; dospělí; senioři; lidé; COVID-19 Vaccines; Adult; COVID-19; transplantace ledvin; ženské pohlaví; vakcíny proti COVID-19; Male; Middle Aged; Kidney Transplantation; protilátky virové; T-lymfocyty; Antibodies, Viral; mužské pohlaví; SARS-CoV-2